2005
DOI: 10.1016/j.dsr2.2005.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of Alexandrium fundyense abundance and shellfish toxicity in the Gulf of Maine

Abstract: Six years of oceanographic surveys of Alexandrium fundyense concentrations in the Gulf of Maine are combined with shellfish toxicity records from coastal monitoring stations to assess covariations of these quantities on seasonal to interannual time scales. Annual mean gulf-wide cell abundance varies by less than one order of magnitude during the time interval examined (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002). Fluctuations in gulf-wide annual mean cell abundance and shellfish toxicity are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 17 publications
(6 reference statements)
2
27
1
Order By: Relevance
“…2). These views are consistent with previous views based on fewer stations and/or years (Anderson, 1997;Hurst and Yentsch, 1981;McGillicuddy et al, 2005b;Shumway et al, 1988). We include them here as they represent a first systematic quantification of these toxicity properties over decadal time scales, over the entire coast and using so many stations.…”
Section: Space and Time Patterns Of Toxicitysupporting
confidence: 92%
See 1 more Smart Citation
“…2). These views are consistent with previous views based on fewer stations and/or years (Anderson, 1997;Hurst and Yentsch, 1981;McGillicuddy et al, 2005b;Shumway et al, 1988). We include them here as they represent a first systematic quantification of these toxicity properties over decadal time scales, over the entire coast and using so many stations.…”
Section: Space and Time Patterns Of Toxicitysupporting
confidence: 92%
“…Within the overall Gulf, seasonal maxima often appear earliest in the west and latest along the east coasts (Anderson, 1997;McGillicuddy et al, 2005c), likely reflecting strong local differences in seasonal warming. Early examinations of toxicity (hereafter, toxicity refers to shellfish toxicity) spatial patterns at four stations over 4 years (Hurst and Yentsch, 1981) show a region of minimum occurrence in the Penobscot Bay region in the center of the Maine coast (Fig.…”
mentioning
confidence: 98%
“…Soft-shell clam settlement peaks in the region typically occur from mid-August to mid-September (Emerson and Grant 1991; Bowen and Hunt 2009). The peak of shellfish toxicities, and thus the timing of toxic blooms, occurs earlier in a southwestward direction along the coast from eastern Maine to Cape Cod, partly reflecting earlier coastal warming and stratification in the western region (Anderson 1997;McGillicuddy et al 2005). Therefore, toxic Alexandrium blooms can co-occur throughout the Gulf of Maine, New England region, with the M. arenaria life-history stage most vulnerable to PSTs, i.e., juveniles less than , 20 mm SL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there has been a well-documented historical southward dispersal of Alexandrium spp. and associated PSP along the coast, most recently, during the massive 2005 bloom, which extended the distribution of PSP in southern New England, thus posing a risk to previously unaffected regions (Anderson et al 2005). Peak spawning and growth rates of M. arenaria also vary latitudinally, leading to potential exposure of all life-history stages to PSP.…”
mentioning
confidence: 99%
“…As an example of the application of currently available investigative monitoring techniques, field and simulation studies in the Gulf of Maine, U.S. (McGillicuddy Jr et al 2005), revealed a number of physical and biological mechanisms which play a key Red tide events in Portuguese coastal waters are unrelated to human use; Changes in estuarine turbidity are unrelated to increased organic production; Given the nature of the Portuguese Atlantic coast, the only state changes in the coastal waters due to basin pressures are in xenobiotics in offshore sediments. H0: Changes in (abiotic) Supporting Quality Elements are not reflected in Biological Quality Elements.…”
Section: The Role Of Target Speciesmentioning
confidence: 99%